Coming Out of the Closet : Young Gay Men's Experiences in the Process of Coming Out - Macdonald, Ronald (1996)
Coming out of the closet is a decision that all young gay men consider, however there has been little recent research undertaken which investigates this phenomenon. The purpose of this qualitative study is to provide an account of young men's experiences in the process of coming out and a critical analysis of the influences of cultural, political and social factors which impinge on the process. A phenomenological method (utilising Colaizzi's procedural steps) will be employed to collect data and to extrapolate common themes and meanings. A purposeful sample of seven young gay men were interviewed. Data was collected from taped interviews and the researcher's field notes. The research findings will add new knowledge to youth studies research as well as providing a basis for ongoing research in the area of gay studies